2009
DOI: 10.3144/expresspolymlett.2009.19
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar crack propagation in MWCNT/fiber reinforced hybrid composites

Abstract: Abstract. In this work carbon fiber/epoxy composites and MWCNT (multiwalled carbon nanotube)/carbon fiber/epoxy hybrid composites with 0.1, 0.3, 0.5 and 1 weight% nanotube filling of the matrix have been prepared and compared in terms of interlaminar properties. For the dispersion of the carbon nanotubes in the epoxy resin three roll milling has been utilized. The mechanical characterization has been carried out using standard DCB (double cantilever beam) tests assisted by acoustic emission. The test results h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 11 publications
2
45
0
Order By: Relevance
“…Since the SWCNT toughening mechanisms postulated above are expected to be more ''active'' during propagation, this supports the idea that these are indeed the source of the increased toughnesses observed. A similar increase of 13% in Mode I fracture toughness was reported by Romhany and Szebenyi [27] for a MWCNT loading of 0.3 wt%, suggesting that SWCNT may be more effective than MWCNT for a given loading. In another work, Karapappas et al [31] demonstrated that 1 wt% loading of MWCNT can result in a 60% improvement in Mode I fracture toughness; however, for small loading of 0.1 wt% (similar to this work) slight reductions in both Mode I and Mode II fracture toughness values were reported.…”
Section: Modes I and Ii Interlaminar Fracture Toughnesssupporting
confidence: 67%
See 2 more Smart Citations
“…Since the SWCNT toughening mechanisms postulated above are expected to be more ''active'' during propagation, this supports the idea that these are indeed the source of the increased toughnesses observed. A similar increase of 13% in Mode I fracture toughness was reported by Romhany and Szebenyi [27] for a MWCNT loading of 0.3 wt%, suggesting that SWCNT may be more effective than MWCNT for a given loading. In another work, Karapappas et al [31] demonstrated that 1 wt% loading of MWCNT can result in a 60% improvement in Mode I fracture toughness; however, for small loading of 0.1 wt% (similar to this work) slight reductions in both Mode I and Mode II fracture toughness values were reported.…”
Section: Modes I and Ii Interlaminar Fracture Toughnesssupporting
confidence: 67%
“…7. This compares to other published results based on MWCNT [26,27] in which the fracture toughness values vary considerably as crack length increases. It seems reasonable that this may be attributable to a more uniform dispersion of SWCNT within epoxy due to a lower loading of SWCNT and the effective functionalization to maintain the dispersion.…”
Section: Modes I and Ii Interlaminar Fracture Toughnesssupporting
confidence: 48%
See 1 more Smart Citation
“…CNT-and CNF-reinforced epoxy nanocomposites have shown improved mechanical, electrical and thermal properties [2][3][4][5]. However, the high cost of CNTs and CNFs and the poor dispersion in the epoxy limits their range of practical applicability.…”
mentioning
confidence: 99%
“…Several studies were already conducted on the mode I fracture to determine the surface energies of composite materials by creating a crack propagation effect [3,4]. To find correlation between AE parameters and damage mechanism several studies have been carried out [5][6][7][8][9]. Most studies so far have used AE descriptors such as counts, amplitude, energy and also multiparameter method to characterize the development of failure mechanisms.…”
Section: Introductionmentioning
confidence: 99%